India in second Coronavirus Disease-2019 pandemic emergency: A brief review - Tarun Vyas (Wolters Kluwer Medknow Publications, 2021)
In a number of countries, coronavirus disease-2019 is a second pandemic that is progressing fast. When it comes to diseases in India, the rate of spread is incredibly high. There has been a slowdown in the use of multifaceted strategies to some extent. Sadly, the disease is advancing rapidly in India despite all efforts. The objective of this review is to evaluate critically the strategies adopted by the Indian Government to address this second pandemic and to propose appropriate strategies for the current context mainly through the 5 T approach (Trace, Track, Test, Treat, and Technology). Local governments have begun to implement disease containment measures, but to explain the need for a mask, a social divergence, stop mass meetings, voluntary quarantines, and testing, the federal government has an essential role to play.